2023
DOI: 10.3390/en16145447
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport Characteristics of Vertical GaN Schottky-Barrier Diode in Reverse Bias and Its Numerical Simulation

Abstract: We investigated the temperature-dependent reverse characteristics (JR-VR-T) of vertical GaN Schottky-barrier diodes with and without a fluorine-implanted edge termination (ET). To understand the device leakage mechanism, temperature-dependent characterizations were performed, and the observed reverse current was modeled through technology computer-aided design. Different levels of current were observed in both forward and reverse biases for the ET and non-ET devices, which suggested a change in the conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Therefore, due to the formation of vacancies and F-vacancy complexes, the number of F at the interstitial site will reduce leading to a reduction in fixed charge density. Our previous study [ 32 ] demonstrated that only approximately 10% of the implanted fluorine exists as fixed negative charges. Therefore, it is necessary to reduce vacancy concentration and increase the F concentration in interstitial sites.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, due to the formation of vacancies and F-vacancy complexes, the number of F at the interstitial site will reduce leading to a reduction in fixed charge density. Our previous study [ 32 ] demonstrated that only approximately 10% of the implanted fluorine exists as fixed negative charges. Therefore, it is necessary to reduce vacancy concentration and increase the F concentration in interstitial sites.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…First-principle defect calculations carried out within the density functional theory (DFT) [ 27 , 28 ] indicate that the dominant defect configuration of F is negatively charged interstitial with the lowest formation energy in n-GaN whereas is the dominant defect in p-GaN. In vertical GaN devices, this property of F has been utilized to improve the BV by spreading the electric field away from the contact edge [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a shows the typical reverse J-V characteristics of the GaN pseudo-vertical SBD. The destructive Breakdwon Voltage BV of the schottky barrier diode is around 80 V, this low voltage capability is mainly related to the absence of edge termination [17,18], and in particular due to expected high electric field at the edges of the Schottky contact. Leakage current in vertical devices has typically been associated with defects in the active layers since the dislocation density is high [11,24], in particular for GaN on Si devices.…”
Section: Reverse Biasmentioning
confidence: 99%
“…Many researchers have reported that variable range hopping (VRH) by dislocations is the main off-state leakage mechanism in vertical GaN diodes on Si, sapphire and GaN substrates [16]. Others have found that the dominant leakage mechanisms in GaN-on-Si SBDs are different at different reverse biases, and depend on the presence of Edge Terminations (ET) [17,18]. This work aims to understand the carrier transport processes in pseudo-vertical Schottky barrier diodes (SBDs) GaN on Si obtained by selective area growth (SAG).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have indicated that variable range hopping (VRH) facilitated by dislocations serves as the principal off-state leakage mechanism in vertical GaN diodes [16]. Others have reported that the primary leakage process in GaN-on-Si SBDs varies for different reverse biases and is contingent upon the presence of edge terminations (ETs) [17,18]. The goal of this study was to understand the carrier transport processes in pseudo-vertical GaN Schottky barrier diodes (SBDs) on Si obtained by Selective Area Growth (SAG).…”
Section: Introductionmentioning
confidence: 99%